2021
DOI: 10.47577/tssj.v17i1.2438
|View full text |Cite
|
Sign up to set email alerts
|

The role of microfinance in funding Small & Medium Enterprises: Harekello Town of Goro Dolla District in Focus, Ethiopia

Abstract: This study examines the role of the Microfinance on funding of the Small and Medium Enterprises (SMEs) in Gorodola Harakallo town. This study was exploring the role of microfinance institutions on small and medium enterprise as well as the extent to which the small business have benefited from the credits scheme of microfinance institution. The specific objectives of this study were as follows; to determine at what extent role of microfinance lead to increase the volume of gross sales of participants and to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The findings above are agreed with the finding of [12] which examines the role of the Microfinance on funding of the Small and Medium Enterprises (SMEs) in Gorodola Harakallo town and the study found out that SMEs have played positive role in improving income, creation of employment and improving the quality of life of the participants of the enterprises in the study area. In addition, the study of Chukwuma [17] conducted empirical study on the impact of credit on small business financing in Florida.…”
Section: Empirical Findings Of the Studysupporting
confidence: 88%
See 1 more Smart Citation
“…The findings above are agreed with the finding of [12] which examines the role of the Microfinance on funding of the Small and Medium Enterprises (SMEs) in Gorodola Harakallo town and the study found out that SMEs have played positive role in improving income, creation of employment and improving the quality of life of the participants of the enterprises in the study area. In addition, the study of Chukwuma [17] conducted empirical study on the impact of credit on small business financing in Florida.…”
Section: Empirical Findings Of the Studysupporting
confidence: 88%
“…Also, Sufiyan, Mengesha and Tasențe [12] come with empirical study which examines the role of the Microfinance on funding of the Small and Medium Enterprises (SMEs) in town. This study was exploring the role of microfinance institutions on small and medium enterprise as well as the extent to which the small business has benefited from the credits scheme of microfinance institution.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…For poor people, these rates indulge them further into unmanageable financial debts. For this reason, Hussen, Wodajo and Tasente and Fanconi and Scheurle indicate that microfinance institutions bridge this capital gap and ensure the smallest unit of society are included in the financial systems [18,26].…”
Section: Helps Entrepreneurshipmentioning
confidence: 99%
“…As such, microcredit reduces to a certain extent the incentive for savings by functioning as a sort of consumer insurance, and incentivize urban residents to diverge their savings into consumption. Microcredit will in a sense alter urban resident consumption structure from savings-focused to consumption-focused [19].…”
Section: Analysis On the Increase Of Urban Resident Consumption By Mi...mentioning
confidence: 99%